The Wiley Blackwell Encyclopedia of Gender and Sexuality Studies 2016
DOI: 10.1002/9781118663219.wbegss588
|View full text |Cite
|
Sign up to set email alerts
|

Militarism and Gender‐Based Violence

Abstract: The relationship between militarism and gender‐based violence is rooted in the gendered socialization of boys and girls. The militarization of masculinities and femininities begins at a young age, reinforcing a gendered division of power and labor and legitimizing the use of political violence. In conflict zones, political violence is often accompanied by gender‐based violence, including sexual assault, rape, sexual slavery, human trafficking, and intimate‐partner violence. Higher rates of violence against wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Various studies have shown that militarism bears material and discursive facets that foster or exacerbate violence against women, reinforce prevailing gendered division, and correlate with higher gender inequality in terms of health, education, political representation, and labor force participation (Bradley, 2018;Elveren & Moghadam, 2022;Enloe, 2014;Sharoni, 2016). In the field of security studies in particular, feminist approaches challenge mainstream distinctions between state, military and society; underlining the downplaying or disregard of non-military threats such as domestic politics, global warming and non-state actors; and highlighting the neglect of women's pervasive insecurities (Adelman, 2017;Hudson, 2016;Pain, 2014).…”
Section: Securitymentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have shown that militarism bears material and discursive facets that foster or exacerbate violence against women, reinforce prevailing gendered division, and correlate with higher gender inequality in terms of health, education, political representation, and labor force participation (Bradley, 2018;Elveren & Moghadam, 2022;Enloe, 2014;Sharoni, 2016). In the field of security studies in particular, feminist approaches challenge mainstream distinctions between state, military and society; underlining the downplaying or disregard of non-military threats such as domestic politics, global warming and non-state actors; and highlighting the neglect of women's pervasive insecurities (Adelman, 2017;Hudson, 2016;Pain, 2014).…”
Section: Securitymentioning
confidence: 99%
“…Moreover, in the context of the pandemic, staying at home has been ascribed a moral meaning, insofar as reducing social contact, and maintaining isolation of the family “bubble” has been equated with consideration for the other ( Strong, 2021 ). Not surprisingly, public spaces of belonging were among the first to disappear once lockdown was imposed, and country after country confined women to their homes, while curtailing their access to help, care, agency, and support, despite the ever-growing flow of complaints about intimate violence.…”
Section: Spacementioning
confidence: 99%
See 1 more Smart Citation
“…These values are placed on masculine ideals, encouraging notions of dominance, aggression, and risk-taking (Kern, 2017;Carroll et al, 2016;McCloskey et al, 2016). Other factors inherent to the military service favouring IPV perpetration include; majority are relatively youthful personnel and at higher risk of heavy alcohol consumption; frequent relocations, and the tendency to objectify the victims (Kwan et al, 2020;Sparrow et al, 2020;2017;Kern, 2017;Sharoni, 2016).…”
Section: Causes / Risk Factors For Ipvmentioning
confidence: 99%
“…Feminists have called attention to the fact that militaristic interpretations of 'national security' and a significant presence of armed military and police personnel paradoxically heighten the sense of insecurity of women and minority groups (Cockburn and Zarkov, 2002;Sharoni, 2008). Additionally, it also appears that societal levels of militarism and rates of sexual assault, rape and intimate-partner violence prior to the escalation of a political conflict impacts upon gender-based violence at the height of the conflict (Sharoni, 2016). Likewise, the prevalence of violence against women during conflict tends to impact on the life experiences and safety of women in post-conflict societies (Cockburn, 2012).…”
Section: Feminist Analyses Of the Relationship Between Political Violmentioning
confidence: 99%